2021
DOI: 10.1016/j.psj.2021.101177
|View full text |Cite
|
Sign up to set email alerts
|

Muscle fiber and fresh meat characteristics of white-striping chicken breasts, and its effects on palatability of sous-vide cooked meat

Abstract: The aim of this study was to compare the histochemical and meat quality characteristics between the normal and white-striping ( WS ) pectoralis major muscles. Additionally, this study investigated the effects of oven cooking ( OV ) and sous-vide ( SV ) cooking methods on objective texture parameters and sensory quality characteristics of the normal and WS chicken breast meats. Results showed that the WS condition broile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…Besides, due to varying heating principles, heating temperatures and other factors, different heating methods affect food organization and structure, which ultimately affect the food taste by changing muscle fiber structure and water contents. Lee et al ( 5 ) found that palatability of white-striping chicken breasts changed after heating and the meat roasted in an oven tasted harder and chewier than that cooked by sous-vide. At present, the research on scallop mainly focuses on the influence of drying method on its flavor and taste substances ( 6 , 7 ); however, there is little research on its cooking method.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, due to varying heating principles, heating temperatures and other factors, different heating methods affect food organization and structure, which ultimately affect the food taste by changing muscle fiber structure and water contents. Lee et al ( 5 ) found that palatability of white-striping chicken breasts changed after heating and the meat roasted in an oven tasted harder and chewier than that cooked by sous-vide. At present, the research on scallop mainly focuses on the influence of drying method on its flavor and taste substances ( 6 , 7 ); however, there is little research on its cooking method.…”
Section: Introductionmentioning
confidence: 99%
“…When using the sous-vide method, meat is generally cooked for a long period of time at 55–80 °C. At relatively low temperatures the juiciness of meat is maintained, while the flavor and tenderness are improved [ 10 ], even in the case of defective meat [ 11 ]. An additional advantage of poultry meat is that it is quite easy to prepare for consumption and is “adaptable” to diverse forms of preparation.…”
Section: Introductionmentioning
confidence: 99%
“…Meat portions can be vacuum-packed with or without spices and other additives, e.g., vegetables or fruit [ 12 ]. The influence of the sous-vide heat treatment method on the technological and sensory qualities of chicken meat is described in the literature [ 11 , 12 ]. However, in these studies the sensory evaluation was carried out to a limited extent.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, WS myopathy occurs primarily in heavier chickens with increased breast yield ( Petracci et al, 2013 ), and is thus more associated with hypertrophic muscle growth than PSE abnormalities ( Lee and Choi, 2021 ). Typically, consumer panelists and trained panelists can visually distinguish fresh samples from the PSE and WS conditions compared to samples from the normal condition, thereby avoiding the purchase of compromised meat ( Kuttappan et al, 2012 ; Lee et al, 2021 ). Marked differences in the meat quality characteristics were exhibited between PSE and normal condition muscles, whereas the occurrence of WS features in chicken breasts was not closely associated with impairing meat quality and cooked texture ( Lee and Choi, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…At 24 h postmortem, the upper surface of the left PM muscle was used to assess the meat color, including lightness ( L *), redness ( a *), and yellowness ( b *), using a Minolta CR-400 chromameter (diffuse D65; illumination C; viewing angle, 0˚; port/viewing area, 8 mm; Minolta Camera Co., Osaka, Japan) according to the recommendations of the Commission Internationale de l'Eclairage ( CIE, 1978 ). After measuring pH and meat color values, meat quality classes were classified by their WS degree, pH 24 h , and L * values, as described previously ( Lee et al, 2021 ; Lee and Choi, 2022 ). The normal group (N = 45) had a pH 24 h value of ≥5.7 and L * value ranging from 48 to 53 without striping, and the PSE group (N = 15) had a pH 24 h value of under 5.7 and L * value of ≥53.0 without striping.…”
Section: Methodsmentioning
confidence: 99%